Student perceptions of COVID-19 challenges affecting student motivation, well-being, and success in undergraduate education - Jonathan F. Prather; Dan McCoy; April Heaney; Laurie A. Smith; Eirin Grimes; Natalie A. Bloomston; Nycole Courtney (PLoS ONE, 2025)
Our objectives in this study were to understand the impact of COVID-19 disruptions on the academic and personal experiences of undergraduate students at a state land-grant institution in the Western United States, and to use those insights to identify actionable ways to improve student success. We used a mixed method survey to assess strategies used by undergraduates to adapt to COVID-19 disruptions. Results revealed that despite challenges, the majority of students continued toward their academic goals. Face-to-face classes yielded the greatest student satisfaction, and students reported great dissatisfaction with separation from peers and instructors. These insights will be especially helpful to educators and administrators in responding to future challenges and planning future approaches. This overview of students’ attitudes associated with moving from in-person to online coursework may also be useful for advising students considering which of these instructional paradigms to pursue.